2016
DOI: 10.1017/rdc.2015.4
|View full text |Cite
|
Sign up to set email alerts
|

Upwelling of Pacific Intermediate Water in the South China Sea Revealed by Coral Radiocarbon Record

Abstract: ABSTRACT. Annual radiocarbon from a massive Porites lutea coral collected from Hon Tre Island, Vietnam, South China Sea (SCS) was analyzed over a~100-yr-long period from AD 1900 to 1986. The pre-bomb results from 1900-1953 show a steady Δ 14 C value of -54.4 ± 1.8‰ (n = 60). These values are similar to coral records located in the central and southern SCS and from Indonesian waters, but are lower than those from Japan. Following the input of anthropogenic bomb 14 C, our results show a sharp increase in Δ 14 C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 65 publications
(102 reference statements)
0
39
0
Order By: Relevance
“…Hon Tre Island is located on a coastal shelf surrounded by less than 100-m-deep waters (Bolton et al 2016). Comparing with the Con Dao Δ 14 C record reported by Mitsuguchi et al (2007), Δ 14 C in Con Dao is consistently higher than that in Hon Tre Island.…”
Section: Data From Ishigaki Guam and Con Dao By Season And Periodmentioning
confidence: 71%
See 3 more Smart Citations
“…Hon Tre Island is located on a coastal shelf surrounded by less than 100-m-deep waters (Bolton et al 2016). Comparing with the Con Dao Δ 14 C record reported by Mitsuguchi et al (2007), Δ 14 C in Con Dao is consistently higher than that in Hon Tre Island.…”
Section: Data From Ishigaki Guam and Con Dao By Season And Periodmentioning
confidence: 71%
“…Although each point of data from Hon Tre Island is represents annual average of respective years, comparisons are made for other locations in SCS in Figs. 2 and 4b, c. To estimate seasonal changes in the magnitude of Δ 14 C, we referred to the seasonal variation in 1969 in Hon Tre Island reported by Bolton et al (2016). They showed that Δ 14 C in spring/summer is lower than that in autumn/winter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During summer (May–October), southwesterly EASM winds drive surface water to the northeast and cause upwelling of deeper cold, low ∆ 14 C water off the coast of southern Vietnam due to offshore Ekman transport (Figure b). Low Δ 14 C values relative to other records in the region, during both thermonuclear bomb testing (>1950) and the prebomb baseline period, as well as seasonally high Δ 14 C values in the winter, indicate the influence of both summer upwelling and winter advection on Δ 14 C at this site (Bolton et al, ). We therefore use the Δ 14 C proxy of seawater circulation in this study to reconstruct monsoon variability from 1584 to 1950 and to understand its linkages to other aspects of the climate system.…”
Section: Introductionmentioning
confidence: 76%